Spatial distribution pattern and negative density dependence analysis of northern subtropical forest communities in Baohua Mountain - Naiwei Li; Baocheng Wu; Xiangui Yi; Weibing Zhuang; Zhong Wang; Tao Wang (Global Ecology and Conservation)
Negative density dependence (NDD) serves as a crucial regulatory mechanism for maintaining biodiversity in forest ecosystems. Testing intraspecific and interspecific competition is fundamental for understanding species coexistence. To gain insights into plant community assembly in Baohua Mountain (Mt. Baohua) of Jiangsu Province, and population dynamics of the critically endangered species Yulania zenii, a 1 ha forest dynamic plot was established in the Baohua Mountain National Park. Using the pair correlation function combined with random-labeling null models and case-control designs, the spatial distribution patterns and NDD effects of various tree species were examined. Moreover, an interspecific correlation network was employed to explore the interactions among dominant species. The spatial point pattern analysis revealed that the overall distribution pattern in Mt. Baohua was aggregated at short distances and became random beyond 20 m; while that of individuals differed across age stages. After accounting for habitat heterogeneity, the spatial distribution of juveniles became less aggregated, and approached randomness at certain distances. The random-labeling null model results indicated that only six and four species exhibited thinning and self-thinning effects at individual scales, respectively. This suggested that NDD is not widespread in Mt. Baohua and operates at irregular scales. Specifically, Yulania zenii exhibited a random distribution at all distances, with no significant NDD effects. Moreover, the correlation network revealed a slightly higher frequency of negative interspecific relationships compared to positive ones, implying stronger interspecific competition than cooccurrence. Yulania zenii showed negative associations in abundance with multiple species, indicating that interspecific competition may constrain its population expansion. This study enhances our understanding of species coexistence mechanisms in northern subtropical evergreen and deciduous broad-leaved mixed forests in China and provides a scientific basis for the conservation of Yulania zenii.